Undergraduate Students’ Perceptions towards the Process of Writing - Maghfiroh Agustinasari Suprapto; Amira Wahyu Anditasari; Siti Kholija Sitompul; Lestari Setyowati (Journal of English Language Teaching and Linguistics, 2022)
Writing process has been proven to be an effective approach to enhance students’ writing performance. The writing process consists of pre-writing, drafting, revising, and editing. The writing process aids the students in developing ideas while writing, but it was claimed that students also face challenges during the process. Therefore, this current study aimed to investigate the students’ perceptions of the writing process and the challenges. The subjects taken were the first-year students of the English Educational program at the State University of Malang, in which 31 students of IC Writing Class were chosen. The perceptions were investigated through a survey study by distributing online questionnaires via Google Form. The questionnaire was divided into four aspects; pre-writing, drafting, revising, and editing, which aimed at exploring the students’ perceptions during the writing process and its challenges. The findings of the study showed that the students experienced difficulties in the writing process. The most challenging stages they had were the pre-writing and revising stage. The students faced challenges in generating and structuring ideas, respectively. Meanwhile, the students claimed that drafting and editing were less challenging since they followed the preceding stage. Nonetheless, the students also believed that proofreading was a complex process in the editing stage. The results of this study will be beneficial for English teachers and future researchers to vary the teaching methodology and reflect a better analysis.